Characterization ofantifungal properties of lipopeptide-producing Bacillus velezensis strains and their proteome-based response to the phytopathogens, Diaporthe spp - Akintayo, Stephen Olusanmi; Hosseini, Behnoush; Vahidinasab, Maliheh; Messmer, Marc; Pfannstiel, Jens; Bertsche, Ute; Hubel, Philipp; Henkel, Marius; Hausmann, Rudolf; Voegele, Ralf T.; Lilge, Lars (Frontiers in Bioengineering and Biotechnology, 2023)
B. velezensis strains are of interest in agricultural applications due to their beneficial interactions with plants, notable through their antimicrobial activity. The biocontrol ability of two new lipopeptidesproducing B. velezensis strains ES1-02 and EFSO2-04, against fungal phytopathogens of Diaporthe spp., was evaluated and compared with reference strains QST713 and FZB42. All strains were found to be effective against the plant pathogens, with the new strains showing comparable antifungal activity to QST713 and slightly lower activity than FZB42. Lipopeptide production analysis revealed that all strains produced surfactin, and one lipopeptide of the iturin family, including bacillomycin L by ES1-02 and EFSO2-04, while QST713 and FZB42 produced iturin A and bacillomycin D, respectively.Fengycin production was however only detected in the reference strains. As a result of co-incubation of strain ES1-02 with the antagonistic phytopathogen D. longicolla, an increase in surfactin production of up to 10-fold was observed, making stress induction due to competitors an attractive strategy for This is a provisional file, not the final typeset article surfactin bioproduction. An associated global proteome analysis showed a more detailed overview about the adaptation and response mechanisms of B. velezensis, including an increased abundance of proteins associated with the biosynthesis of antimicrobial compounds. Furthermore, higher abundance was determined for proteins associated with oxidative, nitrosative, and general stress response. In contrast, proteins involved in phosphate uptake, amino acid transport, and translation were decreased in abundance. Altogether, this study provides new insights into the physiological adaptation of lipopeptide-producing B. velezensis strains, which show the potential for use as biocontrol agents with respect to phytopathogenic fungi.